India's economic reforms and development essays for Manmohan Singh - Ahluwalia Isher Judge; Little I M D (Oxford OUP, 2003)
This collection of essays by fifteen distinguished economists is in honour of Dr Manmohan Singh, and focuses on the reforms he initiated, and on what remains to be done if their benefits are to be realized.
Keywords: Economic development; India